A proposed Model for taxation for corporate profits in the General Tax Authority: a Practical Study - Abdulahad, Alaa Fareed (International Journal of Psychosocial Rehabilitation, 2020)
Tax accounting is one of the methods adopted in the tax screening process in the countries of the world to determine the income of companies and measure income tax, the research aims to propose a model of tax accounting in the General Authority of Taxation in Iraq as a method of accounting for the activities of the taxpayers and follow up the results of their work according to an audit program prepared for this purpose subject to a select sample of tax examiners over the course of a financial year to determine taxable income based on the financial statements of the company approved by the auditors in order to enhance confidence between the financial authority Taxpayers and auditors by using the self-assessment method of tax calculation. These samples are determined annually over a period of time estimated by the tax administration according to the statistical methods of a community of companies. To reach the researcher’s conclusions and the most important recommendations in achieving the research hypothesis.